Evaluation of an Ecohealth Approach to Public Health Intervention in Ha Nam, Vietnam. (March 2018) - Pham, Giang; Lam, Steven; Dinh-Xuan, Tung; Nguyen-Viet, Hung
Abstract : Context: Ecohealth is a transdisciplinary research approach that considers socio-economic, cultural, and environmental factors. Ecohealth program assessment is sometimes unable to capture the process of change, especially when the evidence is not well documented. As such, there is a need to better understand how ecohealth approaches are understood, integrated, and adapted in practice to support the sustainability of the approach. Objective: To evaluate the use of an ecohealth approach to a community-based intervention to improve environmental sanitation and draw lessons learned for similar public health initiatives. Design: An iterative evaluation approach involving 27 in-depth interviews and 9 focus group discussions was used to gather feedback on the intervention activities and outcomes from all participants. Setting and Participants: The study site was Hoang Tay commune, Kim Bang district, Ha Nam province. The participants included 12 farmers, 4 local policy makers, and 7 researchers from Hanoi University of Public Health. Results: The farmers provided specific shortcomings of the biogas procedure steps, while the local authorities identified new and more effective ways to promote sanitation guidelines. Outcomes, as behavior changes, in 3 participant groups were captured. Conclusion: Participation in ecohealth interventions should be collegial to give opportunities for all related stakeholders to build capacity, support, and achieve the transdisciplinary principle. This also helps ensure that the community-based solutions are incorporated in public health interventions. Participatory monitoring and evaluation should support the understanding of the implementation process to capture intervention outcomes.